Internet Health Information–Seeking Trend of Urinary Incontinence in Mainland China: Infodemiology Study - Shuangquan Lin; Lingxing Duan; Xiongbing Lu; Haichao Chao; Xi Wen; Shanzun Wei (JMIR Formative Research)
Abstract BackgroundUrinary incontinence (UI) is a series of clinical episodes featuring involuntary urine leakage. UI affects people in terms of their physical, emotional, and cognitive functioning, and the negative perceptions and impact on patients are not fully understood. In addition, the true demand for the treatment of UI and related issues is yet to be revealed. ObjectiveThe aim of this study is to examine the online search trend, user demand, and encyclopedia content quality related to UI on a national and regional scale on Baidu search, the major search engine in Mainland China. MethodsThe Baidu Index was queried using UI-related terms for the period from January 2011 to August 2023. The search volume for each term was recorded to analyze the search trend and demographic distributions. For user interest, the demand graph data and trend data were collected and analyzed. ResultsThree search topics were identified with the 18 available UI search keywords. The total Baidu search index for all UI topics was 11,472,745. The annual percent changes (APCs) for the topic Complaint were 1.7% (PPPPPPP ConclusionsWeb-based searching for UI topics has been continuous and traceable since January 2011. Different categorized themes within the UI topic highlight specific demands from various populations, necessitating tailored responses. Although online platforms can offer answers, medical professionals’ involvement is crucial to avoid misdiagnosis and delayed treatment.